Modifications to informed consent in clinical research in times of SARS-COV2: a proposal: Una propuesta (Revista Iberoamericana de Bioética, 2023)
The SARS-CoV-2 pandemic and the resulting diseases, COVID-19, represent a major challenge that tests the response capacity of health institutions, but affects all areas of clinical practice, including research on humans. The high risk of contagion from people in interactions has made all aspects of socialization difficult. Physicians engaged in research have encountered a significant barrier as they consider the possibility of infection from this virus. This article proposes modifications to the informed consent, considering this latent risk of infection, trying to make it understandable and expressed in a clear and simple way for the participants. Likewise, it is considered important to identify the measures extrapolated from clinical care that can be taken to the interaction between researchers and study subjects, seeking the timely identification of cases and the prevention of the disease, with priority in the bioethical considerations of the investigation, in times of uncertainty.
Keywords: bioethics; informed consent; consent form; COVID-19